Optimization of Fermentation and Sensory Quality of Mango Yogurt Using Various Sucrose Concentration Fermented by Lacticaseibaciluus paracasei Strain Shirota - Sayuti, Irda; Darmawati, Darmawati; Jumari, Jumari; Hartanto, Adrian (Universitas Labuhanbatu, 2024)
This research explores the optimization of mango yogurt production, leveraging mango as the primary fermentation ingredient and Lacticaseibacillus paracasei strain Shirota (LcS) as the probiotic inoculum. Traditional yogurt, typically derived from animal milk, faces competition from plant-based alternatives. The research objective is to investigate the impact of inoculum ratios and sucrose concentrations on LcS density and sensory attributes, with a focus on the Substrate to Inoculum Ratio (S/I) as a critical parameter influencing microbial metabolism and population dynamics. Various inoculum ratios (1:1, 1:2, 1:4, 1:8 v/v) and sucrose concentrations (0%, 2.5%, 5%, 7.5%) were applied in mango yogurt production. Results from ANOVA analysis indicated significant differences in LcS density among inoculum ratios (F3,16 = 37.01, P = 0.000) and sucrose concentrations (F3,16 = 19.07, P = 0.000). The 1:2 inoculum ratio and 7.5% sucrose concentration emerged as optimal, as evidenced by stable pH conditions and lactic acid profiles within recommended standards. Sensory analysis, employing a 5-point hedonic scale for color, odor, taste, and texture evaluation, revealed moderate acceptance. In conclusion, this study introduces an innovative approach to mango yogurt production, highlighting the potential of specific inoculum ratios and sucrose concentrations for optimal results. The findings contribute to the broader landscape of plant-based yogurt alternatives, underscoring the need for ongoing refinement to meet commercial standards and ensure consumer satisfaction.